Kinerja Simpang Bersinyal dengan Metode PKJI 2023 dan MKJI 1997 pada Simpang Tiga Jalan Raya Mastrip, Wiyung, Surabaya - Khoirotunni'mah, Dwi; Putra, Kurnia Hadi; Agusdini, Theresia Maria Chandra (Jurnal Talenta Sipil, 2025)
The three-way intersection at Mastrip Highway, Wiyung, is one of the signalized intersections in Surabaya, located in a commercial area and industrial zone that serves as a route for heavy vehicles. It connects the road to the entrance and exit of the toll road. This intersection requires review due to high traffic flow, making it a focal point for congestion during peak hours, exacerbated by existing conditions in the surrounding area that lead to additional congestion at the intersection. Therefore, it is necessary to analyze the intersection's performance to address traffic issues. The goal of this study is to determine the degree of saturation at the intersection under existing conditions and after implementing alternative solutions. Data analysis is based on traffic volume calculations in the field, using the 1997 MKJI and 2023 PKJI methods. The results from the alternative solution of traffic signal management, after prohibiting right turns at intersection A (North) and allowing left turns at intersection B (South) towards intersection C (West), showed a saturation degree of 0.78, compared to a previous value of Dj=1.03 ≥ 0.85. This indicates that the traffic performance at the intersection under existing conditions does not meet the requirements of PKJI 2023 and MKJI 1997. Thus, with proper traffic management and engineering, a satisfactory saturation degree can be achieved.